PENGEMBANGAN LKS BERBASIS ASSESSMENT FOR LEARNING (AFL) TEMAN SEJAWAT UNTUK KEMAMPUAN MATEMATIS SISWA SMP - Aflich Yusnita Fitrianna; Ika Wahyu Anita (Universitas Muhammadiyah Pringsewu, 2017)
Abstract This research aims to obtain Student Worksheet based on AfL in peers for mathematical ability of junior high school students. AfL in peers is using by other students in  formative assessment for feedback and scoring. The design of this study was made to develop teaching materials in the form of student worksheets that contain of assessment aspects. In (R D), which is described in two phases, the first phase in the research and development stage. This research used interview and validation sheets as instruments. Output required of this research has produced teaching materials in the form of students worksheet based AfL that validated by the experts and tested. Student Worksheets based on AfL in peers developed has the main structure there are learning activities and essential tasks, there are comments and score columns in every learning activity and essential tasks. Keywords: Student worksheet, formative assessment, Assessment for Learning (AfL), peers